Arcobacter butzleri Biofilms: Insights into the Genes Beneath Their Formation - Adrián Salazar-Sánchez; Itsaso Baztarrika; Rodrigo Alonso; Aurora Fernández-Astorga; Ilargi Martínez-Ballesteros; Irati Martinez-Malaxetxebarria (Microorganisms, 2022)
Arcobacter butzleri, the most prevalent species of the genus, has the demonstrated ability to adhere to various surfaces through biofilm production. The biofilm formation capability has been related to the expression of certain genes, which have not been characterized in A. butzleri. In order to increase the knowledge of this foodborne pathogen, the aim of this study was to assess the role of six biofilm-associated genes in campylobacteria (flaA, flaB, fliS, luxS, pta and spoT) in the biofilm formation ability of A. butzleri. Knockout mutants were constructed from different foodborne isolates, and static biofilm assays were conducted on polystyrene (PS), reinforced glass and stainless steel. Additionally, motility and Congo red binding assays were performed. In general, mutants in flaAB, fliS and luxS showed a decrease in the biofilm production irrespective of the surface; mutants in spoT showed an increase on stainless steel, and mutants in pta and spoT showed a decrease on reinforced glass but an increase on PS. Our work sheds light on the biofilm-related pathogenesis of A. butzleri, although future studies are necessary to achieve a satisfactory objective.